Hygrothermal effects on the free vibration characteristics of delaminated composite pretwisted rotating conical shells - Tanmoy BANDYOPADHYAY (The Japan Society of Mechanical Engineers, 2014)
This paper presents a finite element method to investigate the hygrothermal effects on the free vibration characteristics of delaminated carbon-epoxy composite pretwisted rotating conical shells. The generalized dynamic equilibrium equation is derived from Lagrange's equation of motion neglecting Coriolis effect for moderate rotational speed. In the present formulation, an eight-noded isoparametric plate bending element is used based on the Mindlin's theory. The multi-point constraint algorithm has been incorporated to ensure the compatibility of deformation and equilibrium of resultant forces and moments at the delamination crack front. Numerical results have been generated to study the combined effects of temperature and moisture concentration on the natural frequencies of delaminated composite conical shells in respect of twist angle, stacking sequence, rotational speed and location of delamination. The mode shapes for a typical laminate configuration in hygrothermal environment is also presented.